1995
DOI: 10.1017/s003329170003751x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of partial syndrome eating disorders to anorexia nervosa and bulimia nervosa

Abstract: SYNOPSISA variety of sociocultural, familial and individual features associated with the eating disorders were examined in subjects with full syndrome (FS) and partial syndrome (PS) eating disorders and in normal high school students. The EAT-26 was administered to 995 high school students. This was followed by individual interviews with those who scored in the symptomatic range. Fifty-one students with PS eating disorders, 57 students without eating disorders (normal controls) and 30 hospital patients with FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
104
1
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 31 publications
13
104
1
7
Order By: Relevance
“…An EDNOS diagnosis implies that an individual exhibits all the characteristics of anorexia or bulimia with the exception of one symptom or behavior (i.e., has regular menses instead of amenorrhea, weight is in a normal range, less frequent binging, etc.). Research studies have suggested that although individuals with EDNOS do not meet formal diagnostic criteria for AN or BN, these individuals possess clinically significant symptomology warranting professional attention (APA, 1994;Dancyger & Garfinkel, 1995;Franko & Omori, 1999).…”
Section: Definitionmentioning
confidence: 99%
See 4 more Smart Citations
“…An EDNOS diagnosis implies that an individual exhibits all the characteristics of anorexia or bulimia with the exception of one symptom or behavior (i.e., has regular menses instead of amenorrhea, weight is in a normal range, less frequent binging, etc.). Research studies have suggested that although individuals with EDNOS do not meet formal diagnostic criteria for AN or BN, these individuals possess clinically significant symptomology warranting professional attention (APA, 1994;Dancyger & Garfinkel, 1995;Franko & Omori, 1999).…”
Section: Definitionmentioning
confidence: 99%
“…As compared to the overall general population and male college students, research has demonstrated that eating pathology prevalence rates are significantly higher among female college students (Dancyger & Garfinkel, 1995). According to Mintz and Betz (1988), 3% of college women reported clinical levels of bulimia and 69 to 73% engage in dieting behaviors.…”
Section: Prevalence and Age Of Onsetmentioning
confidence: 99%
See 3 more Smart Citations